World economic momentum peaks - Klaus-Jürgen Gern; Philipp Hauber; Stefan Kooths; Ulrich Stolzenburg (Kiel Institute for the World Economy (IfW), 2018)
At the start of 2018 the global economy is in full swing. On a PPP-basis growth in 2017 was 3.9 percent, the highest rate since 2011. While leading indicators point to still robust growth in early 2018, sentiment has recently been negatively affected by increasing uncertainty about the pace of monetary tightening in the US and concerns about the future of global trade. Financial market turbulence in the course of the coming normalization of monetary policies and an escalation of trade conflicts constitute major risks to our baseline forecast of a gradually moderating but still robust world economy. We expect global output to rise by 4.0 percent and 3.8 percent in 2018 and 2019, respectively. The upward revision from our December forecast by 0.1 resp. 0.2 percentage points to a large extent reflects the incorporation into our baseline of the US tax reform. – – Anfang 2018 befindet sich die Weltwirtschaft in einem kräftigen Aufschwung. Im vergangenen Jahr wurde mit 3,9 Prozent die höchste Zuwachsrate der globalen Produktion (gerechnet in Kaufkraftparitäten) seit dem Jahr 2011 verzeichnet. Zuletzt trübte sich die wirtschaftliche Stimmung allerdings etwas ein. Hierzu dürften insbesondere eine zunehmende Unsicherheit über das zu erwartende Tempo der geldpolitischen Straffung in den Vereinigten Staaten und Sorge um den freien Welthandel beigetragen haben. Turbulenzen an den Finanzmärkten im Zuge der anstehenden geldpolitischen Normalisierung und die Eskalation handelspolitischer Konflikte sind gewichtige Risiken für unsere Prognose einer Weltkonjunktur, die in diesem und im nächsten Jahr zwar etwas an Fahrt verliert, aber insgesamt kräftig bleibt. Wir erwarten, dass die Weltproduktion, in den Jahren 2018 und 2019 um 4,0 Prozent bzw. 3,8 Prozent zunehmen wird. Unsere Prognose vom Dezember haben wir für 2018 und 2019 um 0,1 bzw. 0,2 Prozentpunkte erhöht, was nicht zuletzt auf die durch die Steuerreform bedingte Anhebung der Prognose für die Vereinigten Staaten zurückzuführen ist.
Additional information: Short English version, full version available only in German language.
Keywords: 330; advanced economies; emerging economies; monetary policy; Japan; Russia; ASEAN